Training that delivers results : instructional design that aligns with business goals - Handshaw, Dick (ASTD/AMACOM, American Management Association, 2014)
Instructional designers and other training professionals are often stuck in order-taking roles. The company wants training on a specific topic--business writing, behavioral interviewing, customer service--and a one-size-fits-all module is produced. Training That Delivers Results offers a far better way to educate employees. Written by a widely recognized master of instructional design, this practical book helps readers connect learning solutions with strategic business goals. Designers become proactive partners with their clients, collecting data to define problems, developing targeted trainin.